A water permeability model of nano-reinforced cement pastes based on general effective media theory and multifractals. Issue 6 (15th June 2022) - Gao, Yuan; Jing, Hongwen; Zhou, Zefu; Shi, Xinshuai; Zhao, Zhenlong
Abstract : A theoretical model to predict the water permeability of nano-reinforced cement pastes from the pore structure (including the pore size distribution, pore interconnection, porosity and microcracks) is presented. The model is based on the general effective media (GEM) theory and multifractals, considering both the bridging of microcracks and capillary pores and the filling of nano gel pores of cement pastes reinforced with nano-admixtures. To validate the model, water permeability experiments were conducted using a cementitious composite reinforced with graphene oxide and multi-walled carbon nanotubes. The calculated results showed good agreement with the experimental measurements, with a decrease in the maximum error from 67.8% to 9.7% compared with the previously proposed GEM theory. Moreover, the theoretical calculations suggest that the reinforcing roles of nano-admixtures in cement paste to improve permeability-related properties may be mainly due to bridging effects in microcracks and capillary pores, rather than the filling of nano gel pores. The findings of this study enrich understanding of the mechanism of reinforcing cement-based materials with nano-admixtures. In addition, the permeability of cementitious composites can be measured directly, rather than the use if other using time-consuming methods.